ANALISIS PEMASARAN TERNAK SAPI POTONG DI KABUPATEN KUPANG DENGAN PENDEKATAN STRUKTUR, PERILAKU DAN TAMPILAN PASAR - Ferdinand Suek (Politeknik Pertanian Negeri Kupang, 2009)
Study the marketing efficiency of beef cattle trade was conducted in Kupang Regency.This study was carried out by survey method in four villages of two districts. Sixty farmer’s were sampled using simple random sampling method. Six cattle middle traders and four inter-island cattle traders were sampled with a snowball sampling method. Marketing efficiency was analyzed based on data through a market structure, conduct, and performance approach. Result showed that the market structure of beef cattle in Kupang Regency was an imperfect competition in which the price change was higher at the inter island cattle traders level than at the cattlemen level. The price share and the market margin received by the farmer’s were 60.37% and 39.62% of the price paid by the inter island traders, respectively. Therefore, the profit distribution for the middlemen and for the inter island traders were calculated to be 81.07% and 29.01%, respectively. Therefore, it is recommended that the cattlemen should be informed about the importance of forming or supporting a village cooperation unit enterprise such and the importance of forming a cattlemen group in the beef cattle marketing system as efforts to improve the farmer’s bargaining position.Keywords: Beef cattle, marketing efficiency